The Illusion of Forward Motion: Reflections on the Origin and 21st-Century Resurgence of Repetitive Loop Animation - Bantjes, Rod; Devadder, Guido (Cinémas)

(untitled) (Cinémas, 2025)
This two-part essay explores circular, loop-based animation at two pivotal moments in media history: its 19th-century emergence at the advent of the moving image, and its 21st-century reimagining within contemporary art. Rod Bantjes’ reconstructions uncover how spectral illusions, which still elude explanation, were generated by experimental uses of machines, revealing an early form of machine self-reflexivity embedded in the aesthetic and epistemological logic of the devices. Guido Devadder extends this inquiry through artistic research, analyzing how contemporary installations like CourtCirquit reconfigure the structural principles of the phenakistiscope within a digitally mediated, hyper-reflexive context. Together, the two parts argue that the loop is not merely a visual device but a cultural form—reappearing in times of technological upheaval to expose the limits of perception, the illusion of progress, and the recursive entanglements of human and machine vision.